Risk factors and attitudes towards osteoporosis among the Palestinian females in occupied Palestinian territories - Natour, Nihal; Alshawish, Eman (International Journal of Advances in Medicine, 2025)
Background: Osteoporosis is a leading cause of fracture associated mortality and morbidity and its prevention is important for Palestinian society. Methods: A structured questionnaire was distributed to females in Palestinian territories about risk factors for osteoporosis and attitudes towards the diseases. Data was analyzed using SPSS. Results: 92 women participated in this study, among studied women only 7 were postmenopausal, Age was 30.8±12.3 y, BMI is 25.1±6.6 Kg/m2, attitude score was 5.75±1.6. 58% had bachelor’s degree, 44% were teachers, 23.5% were health workers. 65.9% lived in separate houses. Having job was associated with lower attitude towards importance (0.04) of osteoporosis but improved dairy products consumption. The rate of consuming dairy product on regular basis was higher than 50%, but there was high rate of vitamin D deficiency (37%) and low level of physical activity performance (18%). Conclusions: There is high prevalence for osteoporosis risk factors, but high rate of using dairy products and modest attitude towards importance of osteoporosis.